Two Different Methods of Quantification of Oxidized Nicotinamide Adenine Dinucleotide (NAD(+)) and Reduced Nicotinamide Adenine Dinucleotide (NADH) Intracellular Levels: Enzymatic Coupled Cycling Assay and Ultra-performance LiquidChromatography (UPLC)-Mass Spectrometry - Kanamori, Karina S. (Bio-Protocol, 2018)

(untitled) (Bio Protoc)
Current studies on the age-related development of metabolic dysfunction and frailty are each day in more evidence. It is known, as aging progresses, nicotinamide adenine dinucleotide (NAD(+) )levels decrease in an expected physiological process. Recent studies have shown that a reduction in NAD(+) is a key factor for the development of age-associated metabolic decline. Increased NAD(+) levels in vivo results in activation of pro-longevity and health span-related factors. Also, it improves several physiological and metabolic parameters of aging, including muscle function, exercise capacity, glucose tolerance, and cardiac function in mouse models of natural and accelerated aging. Given the importance of monitoring cellular NAD(+) and NADH levels, it is crucial to have a trustful method to do so. This protocol has the purpose of describing the NAD(+) and NADH extraction from tissues and cells in an efficient and widely applicable assay as well as its graphic and quantitative analysis.